Analysis of the influence of bitumen filling on the mechanical characteristics of collapsible wall joints - Huaqiao XU; Junfeng RONG; Haochen MA (Meitan kexue jishu)
In order to study the impact of bitumen filling on the mechanical characteristics of collapsible shaft lining joints, a combination of model testing and numerical calculations was employed. The study focused on the vertical plate retractable shaft wall joint located in the central air shaft of Linhuan Coal Mine of Huaibei Mining Group. The mechanical properties of the compressible wall joint model were tested under three different conditions: unfilled (Group K), filled with asphalt (Group T), and filled with asphalt with a blocked injection pipe (Group TD). Additionally, a fluid-structrue coupling finite element model was established for numerical simulation. The results indicate that, compared to the average ultimate bearing capacity of Group K, the average ultimate bearing capacity of Group T and Group TD increased by 12.81% and 21.51% respectively. The numerical calculation model was found to be feasible. The numerical analysis reveals that the vertical ultimate bearing capacity of Group T and Group TD is 11.04% and 25.84% higher than that of Group K, showing a consistent growth rate with the model test results. Further investigation demonstrates that as the vertical load gradually increases, the vertical stress on the inner and outer vertical plates of Group K increases linearly and eventually stabilizes. The vertical stress of the inner and outer vertical plates in group T did not increase steadily, but the slope of the vertical stress-vertical load curve of the vertical plates was smaller the closer they were to the asphalt overflow, and the slope of the vertical stress-vertical load curve at the same position was affected by the asphalt flow vortexes. Simultaneously, the higher the vertical load, the faster the asphalt flow speed, which makes the influence on the vertical bearing capacity of the shaft wall gradually increase. The increase in dynamic viscosity of asphalt results in a reduction of fluidity and wall shear force, thereby decreasing disturbance and pressure regulation on the vertical plate inside and outside the shaft wall.